Optimization of a Beam Shaping Assembly Design for Boron Neutron Capture Cancer Therapy Facility Based on 30 MeV Cyclotron - I Made Ardana; Kusminarto Kusminarto; Yohannes Sardjono (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
A series of simulations has been carried out using a Monte Carlo N Particle X code to find out the final composition and configuration of a neutron Beam Shaping Assembly (BSA) to moderate the fast neutron flux which is generated from the thick disk-type beryllium target. The final configuration for neutron BSA design included 35 cm lead as reflector, 39 cm alumina as moderator, 8.2 cm lithium fluoride as fast neutron filter and 0.5 cm boron carbide as thermal neutron filter. Bismuth, lead fluoride, and lead were chosen as the aperture, reflector, and gamma shielding, respectively. The disk-type of beryllium target is 19 cm in diameter with 0.5 cm thickness which is covered by copper plate to hold the water pressured coolant. A higher yield of neutron production requires a higher intensity of proton beams, which generate much heats and causes the target material to melt. Therefore, it is useful to consider the temperature distribution on the target material with ﬂowing water coolant by means of computer modeling while designing the target. ANSYS-Fluent code will be used to estimate the thermal transfer and heat calculation in a solid target during beam irradiation. Epithermal neutron flux in the suggested design were 1,03x109 n/cm2 s, with almost all IAEA parameters for BNCT BSA design has been satisfied.